Themes and situations that cause embarrassment among participants in research in which questionnaires or interviews are used - Juliana Dias Reis Pessalacia; Cléa Regina de Oliveira Ribeiro; Dinéia Massuia (Universidad de Antioquia, 2013)
Objective. To recognize the themes and situations that could make research participants feel embarrassed when questionnaires or interviews are used. Methodology. Quantitative and descriptive study, developed in 2008, involving a stratified sample of 1,1149 subjects who qualified the degree of shame in view of potentially embarrassing themes and situations. Results. For the research participants, it is embarrassing to answer questions related to the following themes: betrayal (50%), physical violence (42%), sexual harassment (42%), psychological violence (40%) and death of loved ones (38%). The situations that most frequently causes embarrassment were: start of the survey or interview without requesting informed consent (83%); lack of information about the type of questions that would be addressed (79%), lack of guaranteed anonymity (78%), or use of images (66%) or a recorder (58%). Conclusion. Themes and situations were identified that caused embarrassment among participants in research in which questionnaires or interviews were used, which should be considered in the ethical evaluation of studies.